The Ability of Malay Inhabitants in Urban Villages to Enjoy a Quality Life in Urban Areas: (Keupayaan Penduduk Melayu Kampung Bandar Menikmati Kualiti Hidup di Bandar) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
Rapid urban development has caused Malay inhabitants of urban villages to have to deal, voluntarily or involuntarily, with a changing and complex environment. This study reveals the ability of such Malay villagers to achieve a quality life through environmental adaptation, as well as social and self-readiness. This study was conducted using a quantitative approach, and involved 509 residents from 21 urban villages around the towns of Kangar, Alor Setar and George Town, as respondents. The findings of the study are that the environmental adaptation, as well as social and self-readiness provide a guarantee for quality living to the villagers, and enhance their ability to deal with the pressures of development in their surroundings. Comparisons between urban village areas showed that the residents of urban villages in Kangar have a high ability of achieving a good quality of life (62.1%), followed by Alor Setar (61.9%) and George Town (61.8%). The status of the quality of life among respondents in all three cities is balanced, with a relative difference of about 0.1% to 0.3%, and thus at a moderate level of ability. Urban development in Malaysia provides urban villagers with a balanced ability to adapt to changes in the urban environment.Keywords: ability, quality of life, urban village, Malay